Acute on chronic kidney disease in dogs: Etiology, clinical and clinicopathologic findings, prognostic markers, and survival. (12th October 2020) - Dunaevich, Asia; Chen, Hilla; Musseri, Danielle; Kuzi, Sharon; Mazaki‐Tovi, Michal; Aroch, Itamar; Segev, Gilad
Abstract: Background: Chronic kidney disease (CKD) and acute exacerbation of CKD (ACKD) are common in dogs. Objective: To characterize the etiology, clinical and laboratory findings, and short‐ and long‐term prognosis of dogs with ACKD. Animals: One hundred dogs with ACKD. Methods: Medical records of dogs diagnosed with ACKD admitted to a veterinary teaching hospital were retrospectively reviewed. Results: The most common clinical signs included anorexia (84%), lethargy (77%), vomiting (55%) and diarrhea (37%). Presumptive etiology included inflammatory causes (30%), pyelonephritis (15%), ischemic causes (7%), other (3%), or unknown (45%). Median hospitalization time was 5 days (range, 2‐29 days) and was significantly longer in survivors (6 days; range, 2‐29 days) compared with nonsurvivors (4 days; range, 2‐20 days; P < .001). Mortality rate was 35%. International Renal Interest Society (IRIS) acute kidney injury (AKI) grade at presentation was associated ( P = .009) with short‐term survival, but presumptive etiology was not ( P = .46). On multivariable analysis; respiratory rate ( P = .01), creatine kinase (CK) activity ( P = .005) and serum creatinine concentration (SCR; P = .04) at presentation were associated with short‐term outcome. Median survival time of dogs discharged was 105 days (95% confidence interval [CI], 25‐184), with 35 and 8 dogs surviving up to 6 and 12 months, respectively. Presumptive etiology ( P = .16) and SCR ( P = .59) at discharge were not predictors of long‐term survival. Conclusion and Clinical Importance: Short‐term outcome of dogs with ACKD is comparable to those with AKI but long‐term prognosis is guarded. The IRIS AKI grade at presentation is a prognostic indicator of short‐term outcome.